Effect of mexiletine on glucose and oxygen uptake in rat brain, liver and myocardial tissue in vitro (Revista Española de Fisiología, 1979)
The effect of mexiletine on oxygen and glucose consumption was studied both in homogenate and slices of brain, liver and myocardium of Wistar rats. Oxygen consumption was detected by means of Warburg's manometric techniques, and glucose utilization by the enzymatic method of glucose oxidase. Whilst glucose uptake was not modified in any of the studied preparations, mexiletine promoted a significant increase of oxygen consumption in the homogenized slices, and an inhibition in the intact tissue.